การศึกษาปัจจัยที่มีความสำคัญในการจัดการป่าชุมชนตามความคิดเห็นของประชาชน : กรณีศึกษาป่าชุมชนโคกหนองโน ตำบลหนองโน อำเภอเมือง จังหวัดมหาสารคาม The Significance of The Factors of Community Forest Management as Opined by The People: A Case Study of Kok Nong No - นาเมืองรักษ์, นเรศ; ภูมิแดนดิน, ปวีนา; กางเกตุ, นฤมล; หกสุวรรณ, ดิษยพงษ์ (Chophayom Journal, 2017)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาระดับปัจจัยที่มีความสำคัญในการจัดการป่าชุมชนโคกหนองโน ตามความคิดเห็นของประชาชน เปรียบเทียบระดับปัจจัยที่มีความสำคัญในการจัดการป่าชุมชนโคกหนองโนตามความ คิดเห็นของประชาชน จำแนกตามเพศ อายุ และระยะเวลาในการตั้งครัวเรือน และศึกษาปัญหา อุปสรรคและข้อเสนอแนะของการจัดการป่าชุมชนโคกหนองโน กลุ่มตัวอย่างที่ใช้ในการวิจัยครั้งนี้ ได้แก่ หัวหน้าครัวเรือนหรือตัวแทนครัวเรือนที่มีอายุตั้งแต่ 18 ปีขึ้นไป จำนวน 253 ครัวเรือน ที่อาศัยอยู่ในหมู่บ้านหนองโน หมู่ที่ 1 และหมู่ที่ 5 ตำบลหนองโน อำเภอเมือง จังหวัดมหาสารคาม ที่ได้จากการแทนค่าตารางการกำหนดกลุ่มตัวอย่าง และทำการสุ่มตัวอย่างแบบง่าย จากจำนวนครัวเรือนทั้งหมด 507 ครัวเรือน เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถาม สถิติที่ใช้วิเคราะห์ข้อมูล ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน t-test และ F-test (ANOVA) ผลการวิจัยพบว่า 1. ระดับปัจจัยที่มีความส????าคัญในการจัดการป่าชุมชนโคกหนองโน ตำบลหนองโน อำเภอเมือง จังหวัดมหาสารคาม ตามความคิดเห็นของประชาชน พบว่า ปัจจัยโดยรวมและรายด้านทุกด้านมีความสำคัญในการการจัดการป่าชุมชนโคกหนองโน ตำบลหนองโน อำเภอเมือง จังหวัดมหาสารคาม อยู่ในระดับปานกลาง โดยเรียงลำดับค่าเฉลี่ยจากมากไปน้อย ดังนี้ ปัจจัยด้านการอนุรักษ์ป่าชุมชน ปัจจัยด้านการพัฒนาป่าชุมชน ปัจจัยด้านการควบคุมดูแลป่าชุมชน และปัจจัยด้านการใช้ประโยชน์จากป่าชุมชน 2. การเปรียบเทียบการจัดการป่าชุมชนโคกหนองโน ตำบลหนองโน อำเภอเมือง จังหวัดมหาสารคาม จำแนกตาม เพศ อายุ และระยะเวลาในการตั้งครัวเรือน พบว่า ประชาชนที่มีเพศ อายุ และระยะเวลาในการตั้งครัวเรือนแตกต่างกัน มีการจัดการป่าชุมชนโคกหนองโน ตำบลหนองโน อำเภอเมือง จังหวัดมหาสารคาม ไม่แตกต่างกัน 3. ปัญหา อุปสรรคและข้อเสนอแนะของการจัดการป่าชุมชนโคกหนองโน ตำบลหนองโน อำเภอเมือง จังหวัดมหาสารคาม พบว่า ประชาชนส่วนใหญ่มีความคิดเห็นเกี่ยวกับปัญหา อุปสรรคและข้อเสนอแนะของการจัดการป่าชุมชนโคกหนองโน ตำบลหนองโน อำเภอเมือง จังหวัดมหาสารคาม โดยเรียงลำดับจากความถี่มากไปน้อย 3 อันดับ ดังนี้ ประชาชนส่วนใหญ่ไม่กล้าแสดงออกและไม่มีส่วนร่วมในการแสดงความคิดเกี่ยวกับการพัฒนาป่าชุมชนโคกหนองโน ขาดความรู้ ความเขา้ ใจในการฟื้นฟูป่าชุมชนโคกหนองโน และประชาชนขาดความสนใจ ไม่ค่อยให้ความร่วมมือและขาดจิตสำนึกในการอนุรักษ์ป่าชุมชนโคกหนองโน ความสำคัญ : ปัจจัยการจัดการป่าชุมชน, ป่าชุมชนโคกหนองโน ABSTARCT The purposes of this study were to examine the significance of the factors of Kok Nong No Community Forest management as viewed by the people, to compare the significance of the factors of Kok Nong No Community Forest management as viewed by the people as classified according to gender, age, and the number of years of setting up the households, and to examine problems, obstacles, and recommendations of Kok Nong No Community Forest management. The sample used in the study consisted of 253 household heads or representatives age 18 years and older in the village of Baan Nong No Moo 1 and Moo 5 in Nong No, sub district Maung, district Mahasarakham, province 507 households obtained using representatives from the table to determine and the simple random sampling technique. The instrument used in the study was a questionnaire. The statistics used for analyzing the collected data were frequency, percentage, mean, standard deviation, t-test and F-test (ANOVA). The results of the research revealed that : 1. The significance of the factors of Kok Nong No Community Forest management in Nong No sub - district, Maung district, Mahasarakham province as viewed by the people is the people showed their opinions about the significance of the factors as a whole and in each of all the aspects in Kok Nong No Community Forest management at a high level in this order from the highest to the lowest means : community forest conservation, community forest development, community forest control and care, and community forest utilization. 2. To compare the significance of the factors of Kok Nong No Community Forest management in Nong No sub - district, Maung district, Mahasarakham province as viewed by the people as classified according to gender, age, and the number of years of setting up the households is the people with differences in gender, age, and the number of years of setting up the household did not differently indicated opinions about the significance of factor as a whole and in each aspect in Kok Nong No Community Forest management. 3. To examine problems, obstacles, and recommendations of Kok Nong No Community Forest management in Nong No sub - district, Maung district, Mahasarakham province is the problems, obstacles, and recommendations for Don Chao Pu Community Forest management included: Most people are not assertive and did not participate in the show, thinking about the development of Kok Nong No Community forest. Lack of knowledge and understanding of Kok Nong No Community forest regeneration. The people lacked interests, seldom provided cooperation, and lacked awareness of Kok Nong No Community forest conservation. Keywords : The Factors of Community Forest Management, Kok Nong No Community Forest